Chemical Engineering Allied Fields - International Conference on Fluids and Chemical Engineering FluidsChE 2017, Malaysia, Special Issue, Vol: 3 - Gajendran, Natarajan; Jolius, Gimbun; Ranganathan, Balu (Informatics Publishing Limited, 2017)
The International Conference on Fluids and Chemical Engineering (FluidsChE 2017) organised by Centre for Excellence for Advanced Research in Fluid Flow (CARIFF), Universiti Malaysia Pahang, Malaysia (FluidsChE 2017) aims to provide aplatform to discuss ideas and latest research findings on different disciplines of chemical engineering. 1st FluidsChE 2015 was conducted in Langkawi, Malaysia in November, 2015 which stirred and kindled intellectual minds to make this event a biannual event to disseminate knowledge and findings of chemical engineering fields to the entire world. As an outcome oft he event 60+ research articles are published in reputed journals which are in open access for all spectrums of researchers to gain knowledge. Research publications were sectioned into three volumes, volume -1, 2 and 3. First volume was segmented into these disciplines of fluid flow dynamics, distillation technology and absorption / adsorption technology. Second volume consisted of natural resources product lifecycle, polymer technology and pharmaceutical technology. Third volume contains allied fields of chemical engineering. Researchers from different parts of the world contributed to the knowledge pool. Convergence was seen where researchers from different disciplines collaborated for technology solution support for product development with feasible techno economics with prospects for successful commercialization.